MOTIVASI KERJA, LINGKUNGAN KERJA, DAN KINERJA KARYAWAN PERUSAHAAN ASURANSI X - Saragih, Daniel Edi Gia; Pramudita, Dismas Persada Dewangga (LPPM STIE YKPN Yogyakarta, 2024)
Employee management is an important aspect that needs to be considered by the company. In the field of Human Resource Management, employees are considered an asset that needs to be managed by the company. The importance of employee management is related to the strategic goals that the company has planned and will achieve within a predetermined time. Companies that pay attention to employees well can have a positive impact on the ability to acquire and retain customers, especially in the service sector. Companies that offer insurance services certainly compete to offer a variety of services to potential customers. This study examines one of the insurance company branch offices in Semarang with a total number of employees as a population as well as a saturated sample of 34 people. Motivation and the work environment were investigated for their influence on employee performance. In this study, questionnaires were distributed online to collect data from respondents. The data collected was processed using the multiple linear analysis method, which was carried out using the help of the SPSS version 29 program. The results of this study indicate that work environment and work motivation affect employee performance positively.